The Philosophy of Ethnobotany and the Transformation of Jamasan Pusaka Tradition in the Pendopo of Batang District - Kartika, Ema; Wicaksono, Harto (Humaniora, 2024)
The tradition of jamasan pusaka (heirloom washing), or simply jamasan,  in Batang District involves various types of plants initsrituals. Plants, as part of the local cultural heritage, play an important role in maintaining the balance of parallelism and interrelationship between macrocosm and microcosm. Over time, this tradition has evolved, and this article aims to explorethe relationship and changes in ethnobotanical knowledge within the jamasan practice. It also analyzeshow the immanent and the transcendental functions of plantsare interpreted. Using a qualitative research method with an ethnographic approach, data were collected through observation, interview, and visual documentation. The study identified 19 types of plants involved in the jamasan tradition. These plants , based on local knowledge, hold immanent and transcendental functions that are important for the continuity of the practice. The plants are categorized into mandatory elementsbased on immanent meaning, symbolic meaning, and non-mandatory elements. Jamasan is not merely the washing of heirlooms, butalso serves as a life guide for living meaningfully. Over time,the tradition has undergone transformations, with shifts from sacred to profane functions and from immanent to transcendental meanings. These changes have reconstructed the practice of jamasan in the present day.